2009
DOI: 10.1021/om9001395
|View full text |Cite
|
Sign up to set email alerts
|

Application of Thiol−Ene Chemistry to the Preparation of Carbosilane−Thioether Dendrimers

Abstract: The application of thiol-ene chemistry to the synthesis of new carbosilane-thioether dendrimers is presented in this work. The dendrimers are prepared in a divergent fashion starting with tetravinylsilane as a core, followed by a succession of alternating thiol-ene and Grignard reactions. Vinyl-terminated dendrimers up to the fifth generation were isolated in excellent yields (78-94%). Products were characterized by multinuclear NMR spectroscopy, dynamic light scattering, gel permeation chromatography, and MAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…5e As mentioned above, thiol−ene reactions proceed via a freeradical-based mechanism, and these radicals can be generated from a specific thiol by thermo-or photoinitiation. However, although there are precedents in the literature of thiol−ene reactions with vinylsilanes, 13−20 examples of reactions involving ferrocene-containing monomers difunctionalized with Si−CH CH 2 groups do not exist. Therefore, we could not predict, in principle, which of the two methods of initiation would be the most appropriate in our case.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5e As mentioned above, thiol−ene reactions proceed via a freeradical-based mechanism, and these radicals can be generated from a specific thiol by thermo-or photoinitiation. However, although there are precedents in the literature of thiol−ene reactions with vinylsilanes, 13−20 examples of reactions involving ferrocene-containing monomers difunctionalized with Si−CH CH 2 groups do not exist. Therefore, we could not predict, in principle, which of the two methods of initiation would be the most appropriate in our case.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Once separated, the pure model compound 2 and the macrocyclic dimer 3 were thoroughly characterized by elemental analysis, 1 H, 13 C, and 29 Si NMR spectroscopy, and MALDI-TOF mass spectrometry. Figure 3 shows the 1 H NMR spectra of thiocarbosiloxanes 2 and 3 together with that of their divinyldisiloxane precursor 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thiol-ene reaction is highly efficient, high yielding, and environmentally benign. [15][16][17] Introduction of hyperbranched structure into photosensitive resins could obtain oligomers with low viscosity and high functionality. Although some hyperbranched photosensitive resin has been developed, the hyperbranched polyurethane methacrylate oligomers containing carboxyl groups which have good compatibility with fillers and dyes has been little reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our growing efforts to take advantage of this valuable synthetic tool in organosilicon chemistry, [13][14][15] we now report a new and highly chemoselective reaction in which chlorovinylsilanes react exclusively with thiol-terminated molecules via the thiol-ene reaction. Previous reports in the literature have shown that thiol-terminated compounds, which are inherently nucleophilic, react with chlorosilanes by displacing the chloride atom; 16,17 however, in the wide breadth of the current study, this was not the case.…”
Section: Introductionmentioning
confidence: 99%